Field Performance and Ergonomic Evaluation of Manual Operated Cranking type Rice Transplanter - AWARE, V.V.; CHOUGULE, S.M.; DABHOLKAR, N.R.; KADAM, V.B. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
Rice is generally grown by transplanting seedlings in puddled field conditions. The cost of puddling and transplanting shares 50% of total production cost. Considering the geographic limitations of Konkan region i.e. smaller plot size and hilly terrain, it was necessary to check the feasibility of manually operated transplanter. It was observed that farmers were not willingly ready to have mat type nursery. It was necessary to have a transplanter to be used with the regular seedlings being prepared by farmers. Such type of transplanter (cranking type manually operated) was taken under this study. The field performance of the transplanter was conducted in the puddled field. The result reveals that, average plant to plant spacing was 13.5 cm. Planting depth during testing was 3.25 cm. The numbers of seedlings per hill were 5. The numbers of hills in one square meter area were found as 35 hills m-2. The average field capacity of the machine was found to be 0.029 ha hr-1. The field efficiency of machine was found to be 95.35%. For ergonomic evaluation of manually operated paddy transplanter six subjects were selected. The average age, weight and stature of the subjects were 26.2 years, 63.5 kg and 167.5 cm, respectively. The working heart rate (HR), oxygen consumption (VO2) and energy expenditure (EER) were 129.18 beats min-1, 1.4 l min-1 and 29.22 kJ min-1, respectively. The value of work pulse (DHR), overall discomfort rating (ODR) and body part discomfort score (BPDS) were 39.97 beats min-1, 5.83 and 6.5, respectively, which indicated that the manual operated rice transplanter operation was under ‘heavy’ workload category.